2015
DOI: 10.1371/journal.pone.0137145
|View full text |Cite
|
Sign up to set email alerts
|

Promising Loci and Genes for Yolk and Ovary Weight in Chickens Revealed by a Genome-Wide Association Study

Abstract: Because it serves as the cytoplasm of the oocyte and provides a large amount of reserves, the egg yolk has biological significance for developing embryos. The ovary and its hierarchy of follicles are the main reproductive organs responsible for yolk deposition in chickens. However, the genetic architecture underlying the yolk and ovarian follicle weights remains elusive. Here, we measured the yolk weight (YW) at 11 age points from onset of egg laying to 72 weeks of age and measured the follicle weight (FW) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
32
0
2

Year Published

2016
2016
2025
2025

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 47 publications
3
32
0
2
Order By: Relevance
“…DHRS11 is a novel type of 17 β-hydroxysteroid dehydrogenase to tart part in the synthesis of estrogen and androgen in human [36]. In chicken, DHRS12 has been identified for its plausible function in yolk and follicle developments [37]. CYP3A40, a cytochrome P450 member, hydroxylates testosterone to regulate the metabolism of hormone in medaka [38].…”
Section: Discussionmentioning
confidence: 99%
“…DHRS11 is a novel type of 17 β-hydroxysteroid dehydrogenase to tart part in the synthesis of estrogen and androgen in human [36]. In chicken, DHRS12 has been identified for its plausible function in yolk and follicle developments [37]. CYP3A40, a cytochrome P450 member, hydroxylates testosterone to regulate the metabolism of hormone in medaka [38].…”
Section: Discussionmentioning
confidence: 99%
“…Claire et al identified ACSBG2 as a candidate gene that was significantly related to abdominal fat deposition in chicken [48]. In addition, Sun et al demonstrated that one SNP located in an intron of ACSBG2 was also significantly associated with yolk development in chicken [49]. NFKB2 with one indel in upstream region encodes a protein subunit of the transcription factor complex nuclear factor-kappa-B (NFkB), which regulates the transcription of genes related to cell differentiation and proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…The results obtained from this study show that fGWAS can be useful for manipulating dynamic EW over the entire laying period (based on a moderate to major effect). The fGWAS SNPs that were associated with EW were located on chromosome 1, close to the gene DLEU7, which regulates ovary weight in chickens [14,33]. The SNPs were detected based on the absolute effect sizes using Bayes C(π) ( Table 5) and BL (Table 6) is likely useful for predicting the polygenic risk scores and/or genomic breeding values during genomic selection for longitudinal EW measurements.…”
Section: Discussionmentioning
confidence: 99%